The Place of Biosimilars in the Therapeutic Strategy in Patients with Moderate-to-Severe Plaque Psoriasis - Lesiak, Aleksandra; Narbutt, Joanna; Owczarczyk-Saczonek, Agnieszka B.; Owczarek, Witold; Pastuszczak, Maciej; Reich, Adam; Szepietowski, Jacek; Walecka, Irena; Feldman, Julia M. (Dermatology Review/Przegląd Dermatologiczny, 2025)
According to European guidelines and the Diagnostic and Therapeutic Recommendations of the Polish Dermatological Society (Polskiego Towarzystwa Dermatologicznego, PTD), the therapeutic goal of the treatment of plaque psoriasis is currently full or almost full control of clinical symptoms. In patients with moderate-to-severe plaque psoriasis, systemic therapies are recommended, e.g. phototherapy and pharmacotherapy, including small-molecule synthetic drugs and biological drugs (both reference drugs and biosimilars). According to the PTD recommendations, biological treatment is indicated in patients with moderate-to-severe plaque psoriasis who do not respond to previous therapies. Due to its high efficacy and relatively low risk of adverse effects, biological therapy should be introduced as early as possible and continued for a long time, provided that the benefits outweigh the potential risk. The PTD recommendations do not specify the priority of choosing a specific biological drug, leaving this decision to the attending physician. The choice of a drug is influenced by various factors, both medical, related to the patient, and non-medical, including those related to the health care system. So far, 4 biosimilars have been registered for the treatment of plaque psoriasis, i.e. adalimumab, etanercept, infliximab and ustekinumab. The introduction of biosimilars to the market provides an opportunity to improve access to standard-of-care therapies.